Oral health issues of young adults with severe intellectual and developmental disabilities and caregiver burdens: a qualitative study - Jihyun Lee; Juhea Chang (BMC, 2021)
Abstract Background Oral health maintenance is difficult to be achieved alone by patients with special needs and insufficient self-care skills. This study aims to investigate how the oral health issues of young adults with severe intellectual and developmental disabilities (IDD) affect caregiver burdens. Methods A qualitative research method was employed with semi-structured interviews conducted with 14 maternal caregivers of patients with severe IDD. Eleven young adults had neurofunctional disorders and three had autism spectrum disorders. All recorded data were transcribed verbatim and subjected to thematic analysis. Results Three themes emerged from the main agenda: predisposing oral dysfunction, home care challenges, and professional treatment barriers. The severity of the disabilities had an impact on oral disease risks that increased as patients aged. Participants indicated that, among the daily living activities of their patients, toothbrushing was a particular hardship due to their dysphagia and behavioral issues. Factors impacting on dental treatment indicated by caregivers included social, emotional, and financial circumstances. Conclusions Dysphagia and behavioral issues of adult patients with severe IDD contributed to caregiver burdens in the dental care of the patients. Caregiver burdens and barriers to treatment were mutual factors hindering adequate interventions in dealing with dental problems of the patients.